Risk factors for perioperative cerebral infarction in moyamoya disease: a meta-analysis - Wu, Jincan; Li, Shiju; Liang, Ruixin; Wang, Yanxu; Shi, Fangyuan; Pan, Xiaoming; Chen, Xinyi (Frontiers in Neurology, 2025)
BackgroundThe present study explored the risk factors for cerebral infarction perioperative moyamoya disease by meta-analysis.MethodsThe PubMed, Embase, Cochrane library, Web of science databases were searched for case–control/cohort studies on risk factors for the emergence of cerebral infarction perioperative moyamoya disease, the search was done from the database creation to June 1, 2024, and the data was analyzed by using stata15.0.ResultTen retrospective cohort studies (N = 3,239) were included. Meta-analysis results suggested posterior cerebral artery involvement [OR = 2.62, 95%CI (1.36, 5.06)], preoperative magnetic resonance angiography [OR = 2.81, 95%CI (1.27, 6.22)], previous infarction [OR = 2.52, 95% CI (1.69, 3.75)] were risk factor for the development of cerebral infarction perioperative moyamoya disease.ConclusionThis study proves that posterior cerebral artery involvement and grade of preoperative magnetic resonance angiography is higher, and the previous infarction happened moyamoya disease a risk factor for cerebral infarction. Therefore, people with these risk factors should be intervened in advance to prevent the occurrence of perioperative cerebral infarction.